2017
DOI: 10.1111/1756-185x.13203
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the epidemiology, disease characteristics and management of systemic sclerosis in Australian adults

Abstract: Information on SSc in Australia, particularly unmet healthcare needs, HRQoL and economic burden, is limited. As a heterogenous condition, SSc requires a multi-disciplinary approach to care. Research aimed at quantifying HRQoL and burden of disease in Australia is essential for advocacy and resource allocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 72 publications
2
13
0
Order By: Relevance
“…The association of ATA and ILD was reported globally among Asian, European, Australian, and North American population. 19,[38][39][40] Nonetheless, this association was not detected in certain other countries including Brazil which is also probably linked to a low number of cases. 41 Moreover, ATA was not correlated in either population with lung involvement severity measured by FVC in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of ATA and ILD was reported globally among Asian, European, Australian, and North American population. 19,[38][39][40] Nonetheless, this association was not detected in certain other countries including Brazil which is also probably linked to a low number of cases. 41 Moreover, ATA was not correlated in either population with lung involvement severity measured by FVC in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous cohort-based studies reported that the lcSSc constitute more than half of the patients and the dcSSc percentage was in a range of 18% (Sweden) to 38% (Singapore). 6,7,13,15,16,18,19 Nonetheless, data from data from Chinese and Thai cohorts reported the prevalence of 59.7% and 68.6% for dcSSc, respectively. 20,21 The higher rate of dcSSc in Iranian patients compared to most of the Asian studies can be either due to referral bias or due to genetic variations that need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…12 Another study that yielded similar results is the one conducted in Lugo, Spain, with a global prevalence of 27.7 per 100,000 inhabitants, 77% females. 13 A review made in Australia by Morrisroe et al 14 showed a prevalence of 23.3-86 per 100,000 inhabitants, with female predominance, with a maximum female:male ratio of 5:1. In Detroit (USA), a prevalence of 27.6 per 100,000 inhabitants was estimated, being more frequent in women than in men, with a 4.6:1 ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Interstitial lung disease occurs in more than half of SSc patients, with the symptoms ranging from subclinical lung involvement to major pulmonary disease progressing and even respiratory failure 11,12 . Pulmonary arterial hypertension and hypertensive renal crisis are also commonly found in patients with SSc 13 . Malignancies are reported at an increased rate, but the magnitude of this risk and the type of cancer vary 14…”
Section: Introductionmentioning
confidence: 99%